1983
DOI: 10.1002/chin.198338372
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: OPTICAL ABSORPTION CHARACTERISTICS OF NICKEL(2+) IN MIXED‐ALKALI BORATE GLASSES

Abstract: Die Ligandenfeldstärke, der Racah‐Parameter und der Koordinationszustand des Ni" in Ni‐haltigen gemischtalkalischen Boratgläsem (Li,O‐K,O‐B2O3 und Na2O‐ K,O‐B,O3) werden anhand ihrer spektralen Absorption im Sichtbaren und nahen lR bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…4 T 1g ðGÞ: The band positions reported for the different mixed alkali NaKB glasses corresponding to 6 A 1g ðSÞ ! 4 T 1g ðGÞ transition are also presented in Table 4 [36]. However, they did not report the band positions but concluded that the effect is small.…”
Section: Optical Absorption Studiesmentioning
confidence: 99%
“…4 T 1g ðGÞ: The band positions reported for the different mixed alkali NaKB glasses corresponding to 6 A 1g ðSÞ ! 4 T 1g ðGÞ transition are also presented in Table 4 [36]. However, they did not report the band positions but concluded that the effect is small.…”
Section: Optical Absorption Studiesmentioning
confidence: 99%
“…A single absorption band in near-infrared region is observed in all samples, which are attributed to d-d transition band due to Cu 2+ ions [17]. Cu 2+ undergoes a Jahn-Teller distortion, which leads to the splitting of energy levels in terms of ligand field theory [18]. It is observed that the elongated structures are usually more energetically favoured than the compressed ones [19].…”
Section: Resultsmentioning
confidence: 85%
“…Ahmed et al [15] have found only a small deviation from the linearity in the optical absorption spectral characteristics of Cu 2+ in a couple of mixed alkali borates, with the composition of the alkali elements. However, a systematic study of the spectral characteristics in mixed alkali borate glasses is necessary to evolve a consistent understanding of the mixed alkali effect in borate glasses, as borate glasses undergo interesting structural changes with alkali content.…”
Section: Introductionmentioning
confidence: 97%